Manufacturing method of multilayer inductor
Patent Information
- Application Number
- JP2024023678
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-26
- Filing Date
- 2024-02-20
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2039-11-28
AI Technical Summary
【0023】 本発明によれば、銀粉末を高濃度に含み、且つ、印刷性に優れる銀ペーストを提供すること、及びそのことにより、充填率及び膜密度が高く、高い導電性を示し、且つ、耐マイグレーション性に優れる銀導体膜を提供することができる。
Smart Images

Figure 0007639955000004 
Figure 0007639955000005 
Figure 0007639955000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a sintered silver paste that contains silver powder and is used to form internal and external electrodes in ceramic electronic components such as multilayer ceramic capacitors, inductors, and actuators. [Background technology]
[0002] Conventionally, conductive pastes containing metal powders have been widely used to form internal and external electrodes of electronic components. One of the reasons for this is that, compared with conductive inks using organometallic compounds, conductive pastes containing metal powders can be used with various printing methods such as screen printing, offset printing, gravure printing, inkjet printing, dipping, dispensing, brushing, and spin coating, and can form thick films by a single coating and printing process, making them advantageous in terms of obtaining high conductivity.
[0003] In order to obtain high conductivity, it is preferable that the conductive paste contains a high content of metal powder, and it is also desirable that the coating film obtained by printing the paste is dense and high density. By using a high content of metal powder, reliable conduction can be obtained even in the formation of finer patterns in the future.
[0004] For example, Patent Document 1 (JP Patent Publication No. 2005-174824) discloses an invention that uses metal colloid particles instead of metal powder to obtain a highly dense and conductive film, and uses an organometallic compound in combination with this to fill the gaps between the metal colloid particles with the organometallic compound, thereby increasing the density.
[0005] However, since metal colloid particles and organometallic compounds contain a large amount of organic components, when these are used as the main conductive component, the content of the metal components is lower than that of pastes using metal powders, and therefore a conductor film with low resistivity cannot be obtained. Moreover, it is difficult to deal with the above-mentioned wide variety of printing methods, and if a large amount of binder resin or viscosity modifier is added to the paste to solve this problem, the metal ratio in the coating film will be further reduced.
[0006] On the other hand, when metal powder is used as the conductive component of the paste, a conductive film with low resistivity can be obtained if the content of the metal powder is high, but the higher the content of the metal powder, the worse the printability becomes. Therefore, in the case of silver paste, for example, the highest coating density described in Patent Document 2 is 5.4 g / cm. 3 The maximum coating density described in Patent Document 3 is 5.70 g / cm 3 In addition, Patent Document 4 describes a nickel paste with a dry film density of 6.2 g / cm. 3 Examples are disclosed.
[0007] As described above, when trying to obtain a dense coating film with high conductivity in a conductive paste, printability is sacrificed, and there is a trade-off between the two. Therefore, there is a demand for a conductive paste that can simultaneously achieve dense coating film formation and good printability.
[0008] There are known examples of using two types of silver powder with different particle sizes, large and small, to obtain a dense coating film (Patent Document 5 and Patent Document 6). However, a phenomenon called migration is known to occur, particularly in the case of silver paste that uses silver powder, and the more small-diameter silver powder (e.g., less than 0.5 μm) contained in the silver paste, the more likely migration is to occur.
[0009] Conventionally, various measures have been attempted to suppress migration, such as adding a migration inhibitor containing fluorine to silver paste (Patent Document 7) or adding a mixed powder, alloy powder, or compound powder containing the three elements of copper, tin, and manganese to silver powder (Patent Document 8). [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2005-174824 A [Patent Document 2] JP 2007-131950 A [Patent Document 3] JP 2008-192565 A [Patent Document 4] JP 2004-220807 A [Patent Document 5] JP 2003-280179 A [Patent Document 6] JP 2005-203304 A [Patent Document 7] JP 2014-197483 A [Patent Document 8] International Publication No. 2014 / 061765 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0011] However, adding a large amount of components other than the silver powder as described above to the paste for the purpose of preventing migration is not preferable in terms of obtaining high electrical conductivity.
[0012] Therefore, the object of the present invention is to solve these problems. That is, the object of the present invention is to provide a silver paste containing a high concentration of silver powder and having excellent printability, and thereby to provide a silver conductor film having a high filling rate and film density, high conductivity, and excellent migration resistance. [Means for solving the problem]
[0013] As a result of intensive research to solve the above problems, the present inventors have found that even when the paste contains a high concentration of silver powder, [1] the content of the silver powder relative to the silver paste, [2] the D10 and D50 of the silver powder, [3] the specific surface area of the silver powder, [4] the copper content of the silver powder, [5] the content of the binder resin relative to the silver powder, and [6] the dry film density of the silver paste can be adjusted within a specific range to obtain a dense dry film without sacrificing printability, and by simply containing the minimum necessary copper component in the silver powder, migration can be effectively suppressed. This has led to the completion of the present invention.
[0014] That is, the present invention (1) is a silver paste containing at least silver powder, a binder resin, and an organic solvent, [1]~[6] below: [1] Content C of the silver powder relative to the silver paste AG is 80.00 to 97.00 mass%; [2] When the 10% value and the 50% value in the volume-based cumulative fraction of the laser diffraction particle size distribution measurement of the silver powder are D10 and D50, respectively, D10 is 1.00 to 3.00 μm and D50 is 3.00 to 7.00 μm; [3] The specific surface area S of the silver powder BET 0.10~0.30m 2 / g; [4] The copper content of the silver powder is 10 to 5000 ppm by mass; [5] Content C of the binder resin relative to the silver powder BND is 0.430 to 0.750 mass%; [6] The dry film density of the silver paste is 7.50 g / cm 3 That's it; The present invention provides a silver paste that satisfies all of the above requirements.
[0015] In addition, the present invention (2) relates to the content C of the silver powder in the silver paste. AGThe present invention provides a silver paste according to claim 1, characterized in that the content of the silver in the silver paste is 92.00 to 96.00 mass %.
[0016] The present invention (3) further comprises the following [7]: [7] The silver powder is a spherical powder having an aspect ratio of 1.0 to 1.3; The present invention provides a silver paste according to either (1) or (2), which satisfies the above conditions.
[0017] In addition, the present invention (4) is characterized in that the dry film density is 7.60 g / cm 3 The present invention provides a silver paste according to any one of (1) to (3) characterized by the above.
[0018] The present invention (5) also provides the silver paste according to any one of (1) to (4), wherein the silver powder has a copper content of 30 to 500 ppm by mass.
[0019] The present invention (6) further comprises the following [8]: [8] Content C of the binder resin relative to the silver powder BND is 0.440 to 0.600 mass%; The present invention provides a silver paste according to any one of (1) to (5), which satisfies the above conditions.
[0020] The present invention (7) also provides the silver paste according to any one of (1) to (6), wherein the D10 is 1.20 to 2.00 μm.
[0021] The present invention (8) also provides the silver paste according to any one of (1) to (7), wherein the D50 is 3.90 to 5.00 μm.
[0022] The present invention (9) also provides a silver paste according to any one of (1) to (8), which is used for forming a conductor film by a heat treatment at 700° C. or less. Effect of the Invention
[0023] According to the present invention, it is possible to provide a silver paste containing a high concentration of silver powder and having excellent printability, and thereby to provide a silver conductor film having a high filling rate and film density, high conductivity, and excellent migration resistance. [Brief description of the drawings]
[0024] [Figure 1] FIG. 2 is an external view of a laminated inductor. [Diagram 2] FIG. 2 is an exploded view of an element part of the laminated inductor. [Diagram 3] FIG. 2 is a simplified cross-sectional view taken along axis XX in FIG. 1. [Figure 4] FIG. 4 is a simplified enlarged view of a part of FIG. 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The silver paste of the present invention contains at least silver powder, a binder resin, and an organic solvent, [1] Content C of the silver powder relative to the silver paste AG is 80 to 97 mass %, [2] When the 10% value and the 50% value in the volume-based cumulative fraction of the laser diffraction particle size distribution measurement of the silver powder are D10 and D50, respectively, D10 is 1.00 to 3.00 μm and D50 is 3.00 to 7.00 μm, [3] The specific surface area S of the silver powder BET 0.10~0.30m 2 / g, [4] The copper content of the silver powder is 10 to 5000 ppm by mass, [5] Content C of the binder resin relative to the silver powder BND is 0.430 to 0.750 mass%, [6] The dry film density of the silver paste is 7.50 g / cm 3 More than this This is a silver paste characterized by the above.
[0026] The silver paste of the present invention contains at least silver powder, a binder resin, and an organic solvent.
[0027] The silver powder according to the silver paste of the present invention, that is, the silver powder contained in the silver paste of the present invention, is not particularly limited in shape, particle size, production method, etc. as long as it can satisfy the requirements described below.
[0028] The copper content of the silver powder according to the silver paste of the present invention is 10 to 5000 mass ppm, preferably 30 to 500 mass ppm. When the copper content of the silver powder is in the above range, migration is unlikely to occur. On the other hand, if the copper content of the silver powder is less than the above range, migration is likely to occur. From the viewpoint of migration resistance, there is no upper limit to the copper content, but if it exceeds the above range, the resistivity increases. Therefore, in the present invention, the copper content of the silver powder is in the range of 10 to 5000 mass ppm. In this specification, the symbol "~" indicating a numerical range indicates a range including the numerical values written before and after the symbol "~", unless otherwise specified. That is, for example, the expression "10 to 5000" is synonymous with "10 to 5000" unless otherwise specified.
[0029] The silver powder according to the silver paste of the present invention has a D10 of 1.00 to 3.00 μm and a D50 of 3.00 to 7.00 μm. The silver powder preferably has a D10 of 1.20 to 2.00 μm, and a D50 of 3.90 to 5.00 μm. When the D10 and D50 of the silver powder satisfy the above requirements, the dry film density is increased and the content of small-diameter silver powder that is prone to migration is reduced, so that short circuits between conductor films are effectively suppressed. The D10 and D50 of the silver powder refer to the 10% and 50% values, respectively, of the cumulative volume fraction of the laser diffraction particle size distribution measurement.
[0030] The specific surface area S of the silver powder in the silver paste of the present invention BET 0.10~0.30m 2 / g, preferably 0.12 to 0.20 m 2 / g. The specific surface area of silver powder S BET By keeping S in the above range, the content of small-diameter silver powder, which is prone to migration, is low, so that short circuits between the conductor films are effectively suppressed. BET (m 2 / g) is the specific surface area determined by the BET method in which helium gas is adsorbed on the surface of silver powder.
[0031] The shape of the silver powder may be granular, flake-like, or amorphous, but is preferably spherical. In the present invention, the term "spherical" refers to a particle having an aspect ratio of 50 particles in a field of view in a scanning electron microscope (SEM) observation that is within the range of 1.0 to 1.5. The average aspect ratio is preferably within the range of 1.0 to 1.3.
[0032] In addition, the silver powder in the silver paste of the present invention is preferably a mixed powder in which two or more types of silver powders having different average particle sizes (D50) are mixed. By using a mixed powder made of two or more types of silver powders having different average particle sizes (D50), it becomes easier to obtain a conductor film with a high dry film density and a dense and highly conductive film.
[0033] The silver powder in the silver paste of the present invention is (a) a first silver powder having a D50 in the range of 3.50 to 7.50 μm, preferably 3.70 to 7.50 μm, and particularly preferably 4.00 to 6.00 μm; (b) a second silver powder having a D50 of 0.80 to 2.70 μm, which may be 0.80 to 2.00 μm, and preferably in the range of 0.80 to 1.80 μm; In this case, the specific surface area S BET The various physical quantities such as D50, D10, copper content, etc., of the mixed powder as a whole after mixing two or more types of silver powders may be within the above-mentioned numerical ranges. Note that, since the second silver powder tends to lower the D10 value of the mixed powder as a whole, it is preferable to use the second silver powder whose D10 is adjusted to 0.70 μm or more.
[0034] The binder resin in the silver paste of the present invention is not particularly limited, and examples of the binder resin include those used in ordinary silver pastes. Examples of the binder resin include cellulose, acrylic resin, phenolic resin, epoxy resin, urethane resin, polyester resin, and polyethylene resin.
[0035] The organic solvent for the silver paste of the present invention is not particularly limited, and may be any organic solvent used in ordinary silver pastes. Examples of the organic solvent include alcohol-based, ether-based, ester-based, and hydrocarbon-based organic solvents, water, and mixed solvents thereof.
[0036] The higher the silver content in the silver paste, the more conductive the film can be obtained, but if the silver content is too high, the printability is reduced. AG The silver powder content in the silver paste is 80.00 to 97.00 mass%, preferably 92.00 to 96.00 mass%. By having the silver powder content in the above range, both the electrical conductivity and the printability can be improved. The silver powder content C in the silver paste is AG (% by mass) is the content ratio of silver powder to silver paste calculated by the formula "(silver powder content / silver paste mass) × 100".
[0037] In the silver paste of the present invention, the binder content ratio C to the silver powder BDN is 0.430 to 0.750% by mass, preferably 0.440 to 0.600% by mass. By having the binder content ratio relative to the silver powder within the above range, it is possible to increase the silver content in the silver paste while maintaining good printability. BND (% by mass) is the content ratio (% by mass) of the binder resin relative to the silver powder obtained by the formula "(content of binder resin in silver paste / content of silver powder in silver paste) x 100".
[0038] The dry film density of the silver paste of the present invention is 7.50 g / cm 3The lower limit of the dry film density of the silver paste of the present invention is preferably 7.60 g / cm. 3 , particularly preferably 7.80 g / cm 3 In addition, the upper limit of the dry film density of the silver paste of the present invention is preferably as high as possible as long as the printability is good. 3 ), and taking into consideration workability and productivity, a realistic limit is 8.50 g / cm 3 The upper limit is about 15 mm. In addition, the method for controlling the dry film density can be controlled by a widely known general method, and examples of the method include adjusting the particle size distribution of the silver powder and its surface condition (smoothness, presence or absence of surface treatment, etc.), changing the binder resin or organic solvent used, or changing the type and amount of a dispersant added to the paste. In the present invention, the dry film density refers to the density of a dry film obtained by drying a coating film of the silver paste as it is without applying pressure. In the example described below, the silver paste to be measured is applied to a PET film with a thickness of about 150 μm, and then temporarily dried at 80 ° C. for 10 minutes, and then punched out with the PET film into a circular shape with a diameter of 15 mm. The PET film is further dried at 150 ° C. for 1 hour, and the PET film is peeled off. The mass W and volume V of the obtained dry film are measured to calculate W / V.
[0039] In the silver paste of the present invention, the specific surface area of the silver powder is S BET (m 2 / g), and the content ratio of binder resin to silver powder is C BND (mass%), "C BND / S BET The value of " is preferably 2.00 to 3.40, and more preferably 2.5 to 3.1. BND / S BET When the value of is within the above range, the silver content in the silver paste can be increased while maintaining good printability, and as a result, a conductive film having a high dry film density, denseness, and high conductivity can be easily obtained.
[0040] The silver paste of the present invention satisfies all of the above requirements [1], [2], [3], [4], [5], and [6], thereby making it possible to obtain a dense, highly conductive film and form a conductor film with low resistivity, while also obtaining a conductor film with excellent printability and coating film shape, which also has excellent migration resistance and reduces the occurrence of short circuits between conductor films. In the experimental examples described below, after the silver paste of the present invention is screen-printed on a substrate to be printed, it is evaluated that the closer the contact angle (rectangularity) between the substrate and the coating film is to 90°, the more preferable the coating film shape (printing pattern) and the better the printability.
[0041] In the present invention, the method for producing silver powder is not particularly limited, but for example, the conventionally known atomization method, wet reduction method, CVD method, PVD method as described in Japanese Patent No. 3541939, spray pyrolysis method as described in Japanese Patent Publication No. 63-31522, and "method of pyrolyzing a pyrolytic metal-containing compound in a gas phase" as described in Japanese Patent No. 3812359 can be used to produce silver powder. Among them, the above-mentioned PVD method, spray pyrolysis method, or "method of pyrolyzing a pyrolytic metal-containing compound in a gas phase" is preferable in that it is easy to obtain silver powder that is spherical, highly crystalline, and has a uniform particle size.
[0042] The silver paste of the present invention can appropriately contain, as necessary, glass frit, inorganic compounds such as metal oxides, and additives that are typically used in silver pastes, such as plasticizers, viscosity adjusters, surfactants, dispersants, and oxidizers.
[0043] The silver paste of the present invention is produced in a conventional manner by kneading together silver powder, a binder resin, an organic solvent, and, where necessary, an inorganic oxide, an additive, and the like, and uniformly dispersing them to prepare a paste having a rheology suitable for screen printing and other printing methods.
[0044] The silver paste of the present invention is used for forming internal electrodes, external electrodes, and thick-film conductor circuits in electronic components such as multilayer ceramic capacitors, inductors, actuators, etc. In particular, the silver paste of the present invention is suitably used for forming internal electrodes of powder magnetic core materials, particularly multilayer inductors in which soft magnetic metal particles are used as the magnetic material.
[0045] In order to facilitate understanding of the "printability" in the present invention, a laminated inductor will be taken as an example for explanation below. Typically, a multilayer inductor 10 is composed of an element body 11, and a first external electrode 12 and a second external electrode 13 covering a pair of end faces of the element body 11, as shown in FIG.
[0046] As shown in FIG. 2, the element 11 is constructed by laminating magnetic layers A1 to A20 and internal electrode layers B1 to B17. The magnetic layers A1 to A20 are obtained by kneading core-shell type composite particles, in which the surfaces of soft magnetic iron alloy particles mainly composed of iron are covered with an insulating film made of resin or oxide film, together with an appropriate binder resin and organic solvent to prepare a magnetic paste, which is then formed into a sheet and dried. On the surfaces of the magnetic layers A3 to A19, the internal electrode layers B1 to B17 are formed in a predetermined pattern by a screen printing method. The silver paste of the present invention is used to form these internal electrode layers. One end of the internal electrode layer B1 is exposed on the end face of the magnetic layer A3 and is electrically connected to the external electrode 12, and one end of the internal electrode layer B17 is similarly electrically connected to the external electrode 13. The internal electrode layers B1 to B17 are electrically connected to each other via through-hole electrodes C1 to C16 formed in the thickness direction of the magnetic layers A3 to A19, and the internal electrode layers B1 to B17 are configured in a coil shape in the lamination direction as a whole. When the internal electrode layers B1 to B17 are formed on the magnetic layers A3 to A19, it is preferable that a magnetic layer (not shown) having a shape capable of filling the step caused by the film thickness of the internal electrode layers B1 to B17 is further laminated on the magnetic layers A3 to A19. Then, the element body 11 in which the magnetic layers A1 to A20 and the internal electrode layers B1 to B17 are laminated is subjected to a thermocompression bonding process and sintered at about 700°C, and then external electrodes 11 and 12 are formed on a pair of ends thereof to form a laminated inductor. Here, the external electrodes may be formed using the silver paste of the present invention, or may be formed using a conductive paste mainly composed of nickel or copper.
[0047] The cross section of the laminated inductor of FIG. 1 manufactured in this manner along the XX axis is shown in FIG. 3, and a part of it is enlarged and shown in FIG. 4. Note that both FIG. 3 and FIG. 4 are simplified diagrams and do not necessarily match the contents and structure shown in FIG. 2, including the number of layers. As shown in FIG. 3, the cross section of the internal electrode layer is ideally desired to be rectangular. However, in reality, when the silver paste is applied and printed on the substrate, the viscosity and fluidity of the paste affect the cross section, so that the actual cross section of the internal electrode layer is usually approximately trapezoidal as shown in FIG. 4. To make this shape closer to a rectangle, it is necessary to obtain a paste with high fluidity when printing the paste and high viscosity immediately after printing. However, there are a great number of parameters that must be controlled in the paste, and they affect each other in a complex manner, so it is no exaggeration to say that there are no cases in which the expected results or characteristics are obtained.
[0048] As described above, in this specification, "printability" means not only that the composition exhibits appropriate fluidity when printed by screen printing, gravure printing or the like, but also that the composition quickly exhibits high viscosity after printing, resulting in a coating film (conductor film) that is closer to a rectangular shape.
[0049] The silver paste of the present invention is suitably used as a fired silver paste used to form internal electrodes and external electrodes in ceramic electronic components such as multilayer ceramic capacitors, inductors, actuators, etc. For example, the silver paste of the present invention is used to form a conductor film by heat treatment at 700° C. or less.
[0050] The present invention will be described below based on specific experimental examples, but the present invention is not limited to these. EXAMPLES
[0051] <Manufacturing of silver powder> First, silver powders 1 to 21 listed in Table 1 were prepared based on the spray pyrolysis method described in JP-B-63-31522. That is, for silver powders 6, 8, 13 to 17, and 19 to 21, the copper content in the obtained silver powder was the value listed in the silver powder overall column in Table 1, and the D10 and D50 values were adjusted by spray pyrolysis of an aqueous solution in which silver salt and copper salt were weighed and dissolved, and the collected silver powder was classified. For silver powders 1 to 5, 7, 9 to 12, and 18, the copper content in the obtained silver powder was the value listed in the first silver powder or second silver powder column in Table 1, and the D10 and D50 values were adjusted by spray pyrolysis of an aqueous solution in which silver salt and copper salt were weighed and dissolved, and the collected silver powder was classified. Then, the obtained first silver powder and second silver powder were mixed to obtain a mixed powder as a silver powder. For each silver powder, the 10% value (D10) and 50% value (D50) in the cumulative volume fraction were determined using a laser diffraction particle size distribution analyzer. In addition, the specific surface area (S BET The aspect ratio of 50 randomly selected silver powder particles was measured by SEM (scanning electron microscope) image observation, and the average value was calculated. The results are shown in Table 1.
[0052] [Table 1]
[0053] (Examples 1 to 11 and Comparative Examples 1 to 11) The silver powder shown in Table 1 is mixed with the silver powder shown in Table 2 at the content C AG and ethyl cellulose was added at the content C shown in Table 2. BND The remainder was terpineol (TPO), and these were kneaded to prepare silver paste samples a to u. Next, each of the silver paste samples a to u was applied to a PET film in an area of 20 mm x 20 mm x 151 μm, dried at 80°C for 10 minutes, punched out using a 15 mm diameter punch, and further dried at 150°C for 1 hour. Next, the mass W and volume V of the resulting dried film were measured, and the dry film density was calculated using the formula W / V. The results are shown in Table 2. The acceptable standard for dry film density was 7.50 g / cm. 3 That's all. Next, the silver paste sample was applied and printed onto a ceramic substrate in the shape of a rectangular parallelepiped measuring 60 mm x 0.6 mm x 40 μm, and fired at 650°C in an oxidizing atmosphere (air) to form a conductive film, after which the electrical resistance was measured using a four-terminal method to calculate the resistivity. The results are shown in Table 2. The pass standard for resistivity was set to 2.00 μΩ·cm or less, and preferably 1.90 μΩ·cm or less.
[0054] [Table 2] 1) Content of silver powder in silver paste: (silver powder / silver paste) x 100 2) Ethyl cellulose content relative to silver powder: (Ethyl cellulose / silver powder) x 100
[0055] (Examples 12 to 22, Comparative Examples 12 to 22) A rectangular parallelepiped pattern was formed by screen printing using the silver paste samples a to u obtained above on a magnetic layer with a thickness of 30 μm that had been prepared in advance, and a magnetic layer was printed to fill in the steps due to the thickness of the pattern. Three sets of these were stacked, and magnetic layers for covers were stacked on the top and bottom. Next, the stack was thermocompressed, degreased in an oxidizing atmosphere, and then fired at 650°C to obtain a laminate. Next, the printability was evaluated using the obtained laminate. Specifically, the laminate was cut as shown in Figure 4, the rectangularity of the cross section of the conductive film was observed, and the average value of the angle corresponding to θ in Figure 4 was measured. The results are shown in Table 3. The acceptable standard for printability was 55° or more, and preferably 65° or more. Further, 25 laminates were prepared in the same manner as above, and the short-circuit rate of the laminates was measured. Specifically, electrical resistance was measured between the top and middle layers and between the middle and bottom layers of the three conductive films in the laminate, and this was repeated for the 25 laminates prepared. The ratio of the number of times that electrical continuity occurred to the total number of measurements was regarded as the short-circuit rate. The results are shown in Table 3. The pass standard for the short-circuit rate was set to 3% or less.
[0056] [Table 3]
Claims
1. A method for manufacturing a laminated inductor having a laminate in which a plurality of magnetic layers and internal electrode layers formed on respective surfaces of the magnetic layers are laminated, and external electrode layers formed on end surfaces of the laminate and electrically connected to the internal electrode layers, comprising the steps of: The internal electrode layers are formed using a silver paste that contains at least silver powder, a binder resin, and an organic solvent and satisfies all of the following conditions [1] to [6]: A method for manufacturing a laminated inductor comprising the steps of: [1] The total content C of the silver powder relative to the silver paste AG is 80.00 to 97.00% by mass; [2] When the 10% value and the 50% value in the volume-based cumulative fraction of the laser diffraction particle size distribution measurement of the entire silver powder are D10 and D50, respectively, D10 is 1.00 to 3.00 μm and D50 is 3.00 to 7.00 μm; [3] The specific surface area S of the entire silver powder BET 0.10 to 0.30 m 2 / g; [4] The copper content of the entire silver powder is 10 to 5000 ppm by mass; [5] The content C of the binder resin relative to the total silver powder BND is 0.430 to 0.750 mass%; [6] The dry film density of the silver paste is 7.50 g / cm 3 That's all.
2. 2. The method for manufacturing a laminated inductor according to claim 1, further comprising laminating a magnetic layer on said magnetic layer so as to fill in a step caused by the thickness of said internal electrode layer.
3. 3. The method for manufacturing a laminated inductor according to claim 1, wherein the internal electrode layers are electrically connected to each other via through-hole electrodes formed to penetrate the magnetic layers in a thickness direction.
4. 3. The method for producing a laminated inductor according to claim 1, wherein the laminate is formed by firing at 700[deg.] C. or less.
5. 3. The method for manufacturing a laminated inductor according to claim 1, wherein the silver paste further satisfies the following condition [7]: [7] The silver powder is a spherical powder having an aspect ratio of 1.0 to 1.3 as a whole.
Citation Information
Patent Citations
Production of silver powder
JP1985248803A
Manufacture of metallic powder
JP1998102108A
Photosensitive silver paste and image display unit using the same
JP2003280179A
Conductive paste composition and laminated ceramic capacitor using it
JP2004220807A
Metal-containing paste and interlayer connection method
JP2005019248A